Teaching practices and students’ study methods: an investigation to combact educational poverty - Guasconi, Elisa; Cecalupo, Marta; Asquini, Giorgio (Form@re - Open Journal per la formazione in rete, 2025)
The contribution deepens some exploratory analyses part of a PRIN project involving six Italian universities aimed at catching the professional development needs of middle schools characterized by educational poverty and at building Teacher Professional Development Research interventions together with teachers. After exploring the differences between students’ study abilities, the relationship between teaching practices and learning skills is examined. By administering a questionnaire made up of several scales and a study test to students, it was possible to collect data for the analyses. Results show a significant gap between students’ study skills and led to question the importance of adopting teaching practices to provide them with an essential base to build a solid study method. Pratiche didattiche e metodo di studio: un’indagine esplorativa per contrastare la povertà educativa. Il contributo approfondisce alcune analisi esplorative parte di un progetto PRIN che coinvolge sei università italiane finalizzato a rilevare i bisogni formativi di scuole secondarie di primo grado caratterizzate da situazioni di povertà educativa e a costruire interventi di Ricerca-Formazione insieme agli insegnanti. Dopo aver esplorato le differenze tra le capacità di studio degli studenti, viene approfondita la relazione tra queste e le prassi didattiche. Grazie alla somministrazione di due strumenti, un questionario composto da diverse scale e una prova di studio, è stato possibile raccogliere i dati necessari alle analisi. I risultati mostrano uno scarto significativo tra i risultati degli studenti nella prova e spingono a interrogarsi sull’importanza di adottare prassi didattiche in grado di fornire una base sulla quale costruire un solido metodo di studio.